ИНГЛИЗ ТИЛИНИ ЎҚИТИШ ЖАРАЁНИДА ЎҚУВЧИЛАРГА МАЪНАВИЙ ВА МАДАНИЙ ТАРБИЯ БЕРИШНИНГ ЎЗИГА ҲОС ҲУССУСИЯТЛАРИ - Арзиева, Б.А. (SCIENCE and SOCIETY, 2019)
The article describes the types and essence of education in teaching, the role of up-bringing, improvement of spiritual-cultural labour and vocational education in teaching English for senior students of the 10-11-th grades at secondary schools.